M.V. Development ofpedagogical education in the Kuban and Adygea in 1920-s - Zarema Yanvarbievna Emtyl; Maxim Vladimirovich Vazankov (Вестник Майкопского государственного технологического университета, 2023)
The article examines the content, forms and results of the development of pedagogical education in the Kuban and Adygea in the 1920s on the basis of a wide range of factual material in the context of solving state problems and developing the local socio-cultural environment. On the basis of the research, the authors have concluded that during the investigated period there was no need to talk about the existence of planning principles and a certain system in its organization. In the course of implementing the guidelines of the central authorities for the training of socialist teachers, real local conditions were not taken into account: the low level of literacy of the population, the lack of the necessary financial, material basis, trained personnel and experience in relevant organizational work. The class selection aimed at its proletarianization had a negative effect on the qualitative level of new teachers. As the main result of the development of teacher education, the acquisition of organizational experience necessary for large-scale planned training of personnel, which has been unfolding since the early 1930s has been noted.